(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In analytical groups, quantitative features are mainly used. They are also applied when constructing distribution rows. When grouping, on quantitative characteristics, questions arise about the number of groups and value - the width of the interval. These indicators are interconnected, the more groups are cut, the less the interval, and vice versa.